Impact and acceptability of self-consent procedures for the school-based human papillomavirus vaccine: a mixed-methods study protocol. Issue 3 (3rd March 2018) - Audrey, Suzanne; Batista Ferrer, Harriet; Ferrie, Joanne; Evans, Karen; Bell, Michael; Yates, Julie; Roderick, Marion; MacLeod, John; Hickman, Matthew
Abstract : Introduction: The human papillomavirus (HPV) vaccine, administered in early adolescence, can substantially reduce cervical cancer incidence and mortality. However, lack of written parental consent is a key reason why some young women do not receive the vaccine. The national legal framework allows girls to be vaccinated without parental consent provided they are deemed Gillick competent, but there is some reticence about vaccinating without written parental consent. Self-consent procedures are being implemented in Bristol and South Gloucestershire. This study will examine the implementation, acceptability and impact of these new procedures. Methods and analysis: Statistical analyses of routine data from Public Health England and the Child Health Information System will test if there has been an increase in HPV vaccination uptake in two ways: (a) Is there an increase when comparing before and after the change in our intervention sites? and (b) Does the percentage change in our intervention sites differ from comparison sites (similar to our intervention sites in terms of initial HPV uptake, ethnicity and deprivation levels) in England where no such intervention took place and how? For the process evaluation, we will develop a logic model and use questionnaires, observations and audio-recorded interviews with young women, school nurses, school staff and parents to examine the context, implementation of self-consent and response to the new procedures. Ethics and dissemination: The University of Bristol Faculty of Health Sciences Research Ethics Committee and the National Health Service Health Research Authority provided approvals for the study. We will produce a report with recommendations about self-consent procedures in conjunction with key stakeholders. At least two papers will be written for publication in peer-reviewed journals and for conference presentations. A summary of results will be shared with participating immunisation nurses, school staff, young people and parents as requested. Trial registration number: ISRCTN49086105 ; Pre-results.